2021
DOI: 10.3390/su13031155
|View full text |Cite
|
Sign up to set email alerts
|

Technical Efficiency of Chemical Fertilizer Use and Its Influencing Factors in China’s Rice Production

Abstract: Low technical efficiency and excessive usage of chemical fertilizer in grain production is a problem commonly faced by China and many other developing countries, which leads to serious environment pollution and high environmental governance cost. China is the largest rice producing and consuming country, and several kinds of rice are grown in China and all of which are important edible grain. However, there has been no systematic research on kind difference and provincial difference of technical efficiency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…Generally, the current values of FIs in those eight countries were of three types (value range of about 100–350 kg ha −1 ) with an average of 225 kg ha −1 in the medium type. This result could be considered as the statistical basis of the maximum safe usage of 225 kg ha −1 for chemical fertilizer use, which is recognized by the international community in the field of environmental science 10,27 …”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Generally, the current values of FIs in those eight countries were of three types (value range of about 100–350 kg ha −1 ) with an average of 225 kg ha −1 in the medium type. This result could be considered as the statistical basis of the maximum safe usage of 225 kg ha −1 for chemical fertilizer use, which is recognized by the international community in the field of environmental science 10,27 …”
Section: Resultsmentioning
confidence: 92%
“…They found that, on average, the TEs for four kinds of rice production in 2018 were 0.651, 0.597, 0.623, and 0.538, respectively. 10 Based on the 4281 farm household survey data from 2004 to 2016 in Jiangsu Province, China, and by using the SFA method, Hu et al 19 found that their technical efficiencies of fertilizer use ranged from 0.84 to 0.99 with an average of 0.95, much higher than other studies. The DEA model was defined as the ratio of multi-output and multi-inputs.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The output of rice (0.60) and wheat (1.00) recorded by Aslam and MS through the CCR method can be regarded as the highest productivity to encourage high-yield and appropriate planting methods in specific areas [25]. Sun Zhilu and others used the Tobit model to analyze the influencing factors of TEFU and found that TEFU has significant differences in different varieties and production provinces in rice production in my country [26]. Sapkota, M used the Tobit model to determine the factors affecting corn planting when studying the factors related to the efficiency of corn seed production technology in the central mountainous area of Nepal [27].…”
Section: Production Technical Efficiency Research Toolmentioning
confidence: 99%